The role of simulation in developing surgical skills. - Akhtar,KSN; Chen,A; Standfield,NJ; Gupte,CM (Curr Rev Musculoskelet Med, 2014)
Surgical training has followed the master-apprentice model for centuries but is currently undergoing a paradigm shift. The traditional model is inefficient with no guarantee of case mix, quality, or quantity. There is a growing focus on competency-based medical education in response to restrictions on doctors' working hours and the traditional mantra of "see one, do one, teach one" is being increasingly questioned. The medical profession is subject to more scrutiny than ever before and is facing mounting financial, clinical, and political pressures. Simulation may be a means of addressing these challenges. It provides a way for trainees to practice technical tasks in a protected environment without putting patients at risk and helps to shorten the learning curve. The evidence for simulation-based training in orthopedic surgery using synthetic models, cadavers, and virtual reality simulators is constantly developing, though further work is needed to ensure the transfer of skills to the operating theatre.